Lectures of the Air Corps Tactical School and American Strategic Bombing in World War II - Haun, Phil M. (Kentucky scholarship online., 2019)
In the 1930s the US Air Corps Tactical School (ACTS) articulated the concept of high-altitude daylight precision bombing (HADPB), a coherent yet controversial theory for victory through the independent employment of air forces. The ACTS lectures present a uniquely American theory of strategic bombing later tested in World War II. These lectures, never before published, introduce Air Corps thinking on strategic bombing during the interwar period. Their originality is found in the causal logic for how HADPB operations would lead to victory by the direct attack of vital and vulnerable economic targets.